1994
DOI: 10.1037/0893-3200.8.3.254
|View full text |Cite
|
Sign up to set email alerts
|

Administering justice in the family.

Abstract: Parents' interventions in conflicts of their 2-and 4-year-olds were observed in 40 families. Parents addressed conflict issues 45% of the time, directed interventions to children who had violated siblings' rights or welfare, supported children who had been victims of such violations, and generally supported rules for family interaction. Not all potential rules received equivalent parental support, however. For example, children could tattle, boss, lie, and exclude siblings, whereas rules prohibiting aggression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 22 publications
3
104
0
Order By: Relevance
“…Observers quietly dictated the ongoing behavioral interaction into a tape recorder, which also recorded all participants' language on a second track. The sessions were transcribed using both the recorded language and detailed descriptive accounts of sibling and parent interaction (see Ross, Filyer, Lollis, Perlman, & Martin, 1994). Transcriptions included verbal and physical action codes of individuals' behavior toward one another (e.g., request action, protest) to translate the interactions accurately.…”
Section: Methodsmentioning
confidence: 99%
“…Observers quietly dictated the ongoing behavioral interaction into a tape recorder, which also recorded all participants' language on a second track. The sessions were transcribed using both the recorded language and detailed descriptive accounts of sibling and parent interaction (see Ross, Filyer, Lollis, Perlman, & Martin, 1994). Transcriptions included verbal and physical action codes of individuals' behavior toward one another (e.g., request action, protest) to translate the interactions accurately.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research on the parental role in sibling behavior has shown that parental nonintervention over sibling disputes is common (~45%) despite leading to subsequent sibling conflict (Kramer, Perozynski, & Chung, 1999; Perlman & Ross, 1997; Ross, Filyer, Lollis, Perlman, & Martin, 1994; Perozynski & Kramer, 1999; Siddiqui & Ross, 2004). Harsh and authoritarian parental behavior following sibling disputes also may lead to more conflictual sibling exchanges (McHale, Updegraff, Jackson Newsom, Tucker, & Crouter, 2000).…”
Section: Reducing Sibling Conflict In Maltreated Children Placed In Fmentioning
confidence: 99%
“…For example, in a study by Siegal and Storey (1985) children judged hitting to be a more serious violation than not sharing or not helping. Similarly, research on parental interventions in siblings' conflicts showed that rules that prohibit aggression and promote sharing received more parental support than did rules that prohibit tattling, bossing, lying, and excluding siblings (Ross, Filyer, Lollis, Perlman, & Martin, 1994).…”
mentioning
confidence: 98%